Autoimmune Lymphoproliferative Syndrome-FAS Patients Have an Abnormal Regulatory T Cell (Treg) Phenotype but Display Normal Natural Treg-Suppressive Function on T Cell Proliferation - Mazerolles, Fabienne (Front Immunol, 2018)
OBJECTIVE: Autoimmune lymphoproliferative syndrome (ALPS) with FAS mutation (ALPS-FAS) is a nonmalignant, noninfectious, lymphoproliferative disease with autoimmunity. Given the central role of natural regulatory T cells (nTregs) in the control of lymphoproliferation and autoimmunity, we assessed nTreg-suppressive function in 16 patients with ALPS-FAS. RESULTS: The proportion of CD25(high)CD127(low) Tregs was lower in ALPS-FAS patients than in healthy controls. This subset was correlated with a reduced CD25 expression in CD3(+)CD4(+) T cells from ALPS patients and thus an abnormally low proportion of CD25(high)FOXP3(+) Helios(+) T cells. The ALPS patients also displayed a high proportion of naïve Treg (FOXP3(low)CD45RA(+)) and an unusual subpopulation (CD4(+)CD127(low)CD15s(+)CD45RA(+)). Despite this abnormal phenotype, the CD25(high)CD127(low) Tregs’ suppressive function was unaffected. Furthermore, conventional T cells from FAS-mutated patients showed normal levels of sensitivity to Treg suppression. CONCLUSION: An abnormal Treg phenotype is observed in circulating lymphocytes of ALPS patients. However, these Tregs displayed a normal suppressive function on T effector proliferation in vitro. This is suggesting that lymphoproliferation observed in ALPS patients does not result from Tregs functional defect or T effector cells insensitivity to Tregs suppression.